The Implementation of Character Education through Online Learning During the Pandemic - Muna, Ana Khalimatul; Lestari, Wahyu; Putra, Prisma Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
During the Covid-19 pandemic, learning activities are carried out online. Although through online learning, it is hoped that teachers will still teach character education, considering the importance of character education for the younger generation. This study aimed to analyze the implementation of character education through online learning during the pandemic in elementary school. The research method used is qualitative research with a descriptive approach with data collection techniques through observation and interviews. The subject of the study was the fifth-grade elementary school teacher. The results show that the character education provided by the teacher through the Zoom application is that the teacher familiarizes students with praying and greeting before and after learning begins, the teacher familiarizes students with wearing neat and polite clothes. The teacher gives advice that can foster positive character for students. The teacher provides character education through the WhatsApp application. The teacher sends quotes with character values regularly, familiarizes students with using polite language when sending messages or assigning assignments in groups, and sends videos or video links about character education to students. Based on the study results, it can be concluded that fifth-grade teachers have implemented character education through online learning by utilizing internet-connected applications, namely Zoom and WhatsApp applications.